Coupled measurements of hydraulic permeability and full stiffness tensor compaction trends in artificial shales. Issue 1 (1st December 2018) - Beloborodov, Roman; Pervukhina, Marina; Lebedev, Maxim
Abstract : Understanding of compaction trends of elastic and hydraulic properties in anisotropic shales is crucial for exploration of energy resources, ecological disposal of nuclear waste, and hydrogeological applications. However, complexity of the natural shale mineralogy and lack of quality data available for analysis results in poor knowledge of these compaction trends. Careful control over the shale mineralogy, pore fluid composition and applied stresses allows us to simulate the natural environments and acquire quality data on the properties of artificial shales. Here for the first time we present methodology and describe a setup that allows simultaneous acquisition of all five independent elastic constants and extremely low hydraulic permeability values of transversely isotropic artificial shale samples during mechanical compaction experiments (porosity decrease from 40% to 10%). Hydraulic permeabilities of artificially compacted samples are comparable to the ones of natural shales. Permeability drops exponentially with compaction. Silt fraction and clay mineralogy are the two key parameters that are responsible for broad variations of permeability in shales with the same porosity. We provide analytical equations that allow calculating permeability if porosity and silt fraction are known. Elastic constants of clay matrix exhibit positive linear trends with the porosity decrease. Small variations in clay mineralogy have a minor effect on absolute values of elastic coefficients or anisotropy but lead to noticeable increase of the compressional (VP) to shear (VS) velocities ratio at the same porosity. Finally, strong correlations (R 2 above 0.95) of the hydraulic permeability with acoustic impedance and VP/V S ratio are observed for all the prepared samples.